Pembebanan Preferential Tariff Skema Asean Trade In Goods Agreement (ATIGA) Berdasarkan Operational Certification Procedurs - Fahri, Azmi; Pranacitra, Resi; Santoso, Iman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The ASEAN Trade in Goods Agreement (ATIGA) is a form of an agreement made by ASEAN member countries that is expected to create a coherent and integrated ASEAN economy through the free movement of commodities, while supporting the concept of minimizing and eliminating international trade barriers, both in the form of tariffs and non-tariff. -fare. As a lower tariff facility, ATIGA also requires imported goods to meet certain conditions contained in a package of provisions called the Rules of Origin, which consists of Origin Criteria, Shipping Criteria (Consignment Criteria), and Procedural Provisions. The research was conducted with a normative juridical approach with data collection techniques through library research, with the conclusion that there are still differences in the application of Operational Certification Procedures (OCP) to the imposition of preferential tariffs by the customs administration and the Panel of Judges of the Tax Court in resolving disputes regarding preferential tariffs. Thus, to provide legal certainty, fairness, and benefit to all stakeholders, it is necessary to make adjustments both to the legal product for the implementation of the imposition of preferential tariffs, as well as redesign in determining preferential tariffs through the application of advance rules.